Electrocardiographic Indices in Clinically Healthy Iranian Najdi Goats in Different Ages: A Reference Study - Aliasghar CHALMEH; Seyed Mohamad Mehdi HEIDARI (İstanbul Üniversitesi Veteriner Fakültesi Dergisi, 2015)
The cardiovascular system develops along with growing the animals. Information regarding the alterations of electrocardiographic parameters during aging can provide the basis to evaluate the development of cardiovascular system. Hence, the present study was performed to clarify the effect of aging on electrocardiographic alterations in Iranian Najdi goats. The electrocardiograms were recorded on a bipolar base apex lead from 172 clinically healthy Iranian Najdi does into 9 age groups, including 15-day-old (n=18), 2 (n=18), 6 (n=19), 9-month-old (n=21), 1 (n=20), 2 (n=22), 3 (n=19), 5 (n=18) and 7-year-old (n=17). All electrocardiograms were examined to evaluate normal electrocardiographic parameters and cardiac arrhythmias. Finally changing of the electrocardiographic parameters during aging was statistically determined. P, S and T durations were increased significantly during aging. Furthermore, the significant increases were seen in RR, QT and ST intervals. Sinus tachycardia and sinus arrhythmia were the most common cardiac arrhythmias in studied animals. The proportion of cardiac arrhythmias in under 1-year-old kids was significantly higher than other groups. It may be concluded that aging can affect electrocardiographic parameters in Iranian Najdi goats.